Normal thoracic aortic diameter in thai people by multidetector computed tomography - Euathrongchit J. (2014)
Objective: To determine the normal size of the thoracic aorta among Thai people. Material and Method: The aortic diameter of 73 Thai males and 56 Thai females, in four age groups, were measured from thoracic Multidetector Computed Tomography (MDCT) images. Aortic size were analyzed and correlated by age, sex, and vertebral body. Results: All showed normal aortic configuration, i.e. smooth tapering from aortic root to ascending and descending aorta. Mean aortic diameters were 3.12 cm at proximal ascending aorta, 2.95 cm at distal ascending aorta, 2.59 cm at mid arch, 2.33 cm at proximal descending aorta, 2.14 cm at distal descending aorta, and 2.03 cm at diaphragm. Males' aorta were larger than females, and all levels of the aorta were significantly enlarged with increasing age. Tapering of the vessel ratio of the ascending aorta/distal aorta at diaphragm was 1.5 without statistical significance. There was a weak correlation between aortic size and vertebral body at all levels. Comparing the size of the aorta to that of the vertebrae, the aorta was larger at the ascending part, equal at the mid arch and smaller at the descending part. Conclusion: Among the Northern Thai people, the average size of the aorta was determined at each level. It was found that aortic size is significantly dependent on age, sex, and vertebral body width.